Theology and difference : the wound of reason - Lowe, Walter James, 1940- (Indiana University Press, 1993)
Theology and Difference reconceives the options confronting modern theology and investigates the disputed questions that underlie it. Pressing beyond the ready-made enlightenment offered by the subject-object framework, Walter Lowe uncovers a number of remarkable convergences between the contemporary philosopher Jacques Derrida and the early twentieth-century theologian Karl Barth. --From publisher's description.
Keywords: Theology -- Methodology.; Theology.; Theodicy.; Deconstruction.; Faith and reason.; Deconstructivism (Architecture); Théologie -- Méthodologie.; Théologie.; Théodicée.; Déconstruction.; Foi et raison.; Déconstructivisme (Architecture); theology.; Deconstructivist.; deconstruction (theory); RELIGION -- Christianity -- General.; RELIGION -- Cults.; Deconstruction; Faith and reason; Theodicy; Theology; Theology -- Methodology; Theodicee.; Godsdienstfilosofie.